Emotional Reactions and Adaptation to COVID-19 Lockdown (or Confinement) by Spanish Competitive Athletes: Some Lesson for the Future - Jaenes Sánchez, José Carlos; Alarcón Rubio, David; Trujillo, Manuel; Peñaloza Gómez, Rafael; Mehrsafar, Amir Hossien; Chirico, Andrea; Giancamilli, Francesco; Lucidi, Fabio (Frontiers in Psychology, 2021)
The Coronavirus Covid 19 (SARS-CoV-2) pandemic has produced terrible effects in the world economy and is shaking social and political stability around the world. The world of sport has obviously been severely affected by the pandemic, as authorities progressively canceled all level of competitions, including the 2020 Olympic Games in Tokyo. In Spain, the initial government-lockdown closed the Sports High-performance Centers, and many other sports facilities. In order to support athlete's health and performance at crises like these, an online questionnaire named RECOVID-19, was designed to assess how athletes were living their lives during such periods of home confinement. The main purpose of the questionnaire was to assess the impact of prolongued confinement on athlete's psychological, emotional, and behavioral performance. One thousand, two hundred forty-eight athletes participated in the survey. They had the fllowing characteristics: (Mean age = 22.31 ± 11.49, Female: 53%), who compete at National (N: 1017, Mean age = 21.58 ± 11.42, Female: 52%) and International level (N: 231, Mean age = 25.56 ± 11.22, Female: 57%). Results showed that during the confinement period, those athletes who lacked motivation reported a higher level of stressful thoughts, more behavioral problems, and greater emotional upheaval (anger, fatigue, tension, and depression). However, those athletes who accepted confinement measures as necessary, and were in favor of respecting the rules of social isolation, fostered positive emotional states such as feelings of friendship. In addition, the availability of some sport equipment together with the ability to continue some training, were (1) protective factors against emotional stress, lack of motivation and behavioral problems; and (2) they were associated with greater respect for, and adherence to, confinement rules. Gender differences, tested by multigroup analysis, revealed that coping activities were more often associated to negative emotional states among women, whereas the ongoing availability of training information and future conditions were equally protective factors for both genders. This study also showed that receiving coaching, support and completing frequent training routines seem to be valuable tools to prevent or reduce some of the harmful effects of isolation on athlete's emotional well-being. The conclusions derived from this research would possibly help sport authorities to design supporting policies and plans to support athletes and trainers in future disruptive health crises.